The development of prose in Tunisia during the French protectorate - Koptileuova D Т (Journal of Oriental Studies, 2016)
The origin of Arabic literature of the new Tunisia dates back to the second half of the XIX century. and is closely linked with the growth of social and economic reforms in the country, formation of national consciousness of Tunisians. The most widely received genre of the short story, the base of which is connected with the names of Zein al-Abdin al-snus, Muhammad әl-Bashrush Mahmoud Bayram al-Tunisi, Ali al-Duadzhi and others.